2000
DOI: 10.1017/s1047951100006557
|View full text |Cite
|
Sign up to set email alerts
|

Effect of physical training in children and adolescents with congenital heart disease

Abstract: In order to test the effect of systematic supervised physical training, we divided a total of 129 children and adolescents with congenital heart disease into a group undergoing intervention and a control group. All patients underwent exercise tests, measurements of physical activity, and a survey of psychosocial factors. An improvement in uptake of peak level of oxygen was observed after intervention. There was also an improvement in physical activity in both groups measured by a monitor, although this was sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
95
1
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(102 citation statements)
references
References 10 publications
5
95
1
1
Order By: Relevance
“…These findings have led to calls for the provision of exercise-based programmes of rehabilitation. 6,7 Few studies have directly sought the views of young people with congenital cardiac disease or their parents. Studies with parents 8,9 show that they experience raised levels of psychological distress, and less adequate strategies for coping, in comparison to normative reference groups.…”
Section: O Ver the Last Decade There Has Been Anmentioning
confidence: 99%
“…These findings have led to calls for the provision of exercise-based programmes of rehabilitation. 6,7 Few studies have directly sought the views of young people with congenital cardiac disease or their parents. Studies with parents 8,9 show that they experience raised levels of psychological distress, and less adequate strategies for coping, in comparison to normative reference groups.…”
Section: O Ver the Last Decade There Has Been Anmentioning
confidence: 99%
“…More recent reviews concluded that a number showed worthwhile change in work capacity, self-esteem and psychological status, but recruitment and retention of patients is a major problem. 14,15 Much of the research into congenital cardiac disease is very medical in its approach, and also relies heavily on the parental perspective of the child's condition. A study by Lightfoot et al 16 investigated the views of pupils, parents, and teachers regarding the service support needs of pupils with a chronic physical condition in mainstream schools, including some children with congenital cardiac disease.…”
mentioning
confidence: 99%
“…In the work of O.I. Yankelevich [12] it is noted that posture disorders were found in more than 50% of examined before hospitalizing children with CHD: scoliotic posture; slouch; scoliosis of 1 st , 2 nd and 3 rd category. In the research of L.V.…”
Section: Pedagogics Psychologymentioning
confidence: 99%
“…Scientists note that patients with FOV lag in physical development [3] have reduced functional potentials of respiratory system [9,12,19,22] and tolerance to physical loads [11,14,24,30]. As on to day the problems of physical rehabilitation of children with CHD are paid insufficient attention to.…”
mentioning
confidence: 99%